Protective effect of histidine on para-nonylphenol-enhanced hydroxyl free radical generation induced by 1-methyl-4-phenylpyridinium ion (MPP +) in rat striatum - Obata, Toshio; Kubota, Shunichiro; Yamanaka, Yasumitsu (Biochimica et biophysica acta, 2001)
The present study examined the antioxidant effect of histidine, a singlet oxygen ( 1O 2) scavenger, on para-nonylphenol (an environmental estrogen-like chemical)-enhanced hydroxyl radical (·OH) generation induced by 1-methyl-4-phenylpyridinium ion (MPP +) in extracellular fluid of rat striatum. Rats were anesthetized, and sodium salicylate in Ringer’s solution (0.5 nmol/μl/min) was infused through a microdialysis probe to detect the generation of ·OH as reflected by the non-enzymatic formation of 2,3-dihydroxybenzoic acid (DHBA) in the striatum. Introduction of para-nonylphenol (10 μM) significantly enhanced MPP +-induced ·OH generation. Histidine (25 mM) decreased the para-nonylphenol-enhanced ·OH formation. Although the level of MPP +-induced ·OH formation trapped as DHBA after para-nonylphenol treatment increased, para-nonylphenol failed to increase either the level of dopamine and DHBA formation in the reserpinized animals. These results indicate that para-nonylphenol and MPP +-enhanced ·OH generation was based on 1O 2 production, and histidine may have a preventive effect on para-nonylphenol and MPP +-induced ·OH generation in rat striatum.